Analisis Pengaruh Current Ratio, Debt to Equity Ratio, dan Working Capital Turnover terhadap ROA Perusahaan Makanan dan Minuman di BEI 2020-2024 - Ainun Fadhila; Erna Puspita; Andy Kurniawan (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Food and beverage companies play a vital role in the Indonesian economy, despite facing various challenges such as fluctuating raw material prices and intense market competition. Return on Assets (ROA) is used as an indicator to assess a company's profitability performance, which is crucial for determining the extent to which a company can generate profits from its assets. This study aims to analyze the effect of three financial variables, namely the current ratio (CR), debt to equity ratio (DER), and working capital turnover (WCT), on return on assets in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The approach used in this study is a quantitative approach with data analysis techniques that include classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests. The sample used in this study was 31 food and beverage companies selected using purposive sampling techniques based on certain criteria. The results of the study indicate that (1) debt to equity ratio and working capital turnover partially have a significant effect on return on assets, while the current ratio does not have a significant effect on return on assets. (2) Simultaneously, the current ratio, debt to equity ratio, and working capital turnover have a significant effect on return on assets in food and beverage companies listed on the IDX. The findings of this study state that the DER and WCT variables have a strong influence on ROA, which means that both are important factors in improving the profitability performance of companies in the food and beverage sector. Thus, the results of this study can provide insight for company managers and investors in making decisions related to financial management to maximize company profitability.